Conceptual Review Forward RSM Design Approach: Integrasi Lean Six Sigma, Sprint dan Extreme Programming - Muhammad Dwi Hary Sandy; Lubis, Muharman (Electronic Integrated Computer Algorithm Journal, 2025)
The Recognize, Scrutinize, and Materialize (RSM) Design Approach has evolved into an important framework for addressing diverse challenges in design and innovation across a variety of industries. by combining methodologies such as Lean Six Sigma, Sprint and Extreme Programming, creating customized variants to meet specific domain needs. This study highlights the application of RSM in various case studies, including education, healthcare, digital ecosystems, and business process optimization. Key results show reduced development timelines, increased user engagement, and increased process efficiency. Additionally, the integration of sustainability metrics into the Materialization phase ensures environmentally responsible design. This research underscores the adaptability and relevance of RSM in addressing modern challenges, providing a foundation for future advances in user-cantered design and iterative methodologies.